Kualitas Fisik dan Protein Telur Ayam Ras dengan Pemberian Virgini Coconut Oil dan Minyak Zaitun serta Lama Penyimpanan yang Berbeda - Irmawaty Majid; Amelinda Amda Dwiputri; Muhammad Nur Hidayat; Khaerani Kiramang (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine whether the type of oil and storage time can affect the physical and protein quality of layer eggs and whether there is an interaction between these two factors. This study used 36 Lohmann brown chicken eggs. The research method used a completely randomized design (CRD) with a 2x3x3 factorial pattern where 2 treatments were factor A (type of oil) and 3 treatments were factor B (storage time) using 3 repetitions. Factor A consists of M1 (Coconut Oil) and M2 (Olive Oil) while factor B consists of P1 (storage 7 days), P2 (storage 14 days) and P3 (storage 21 days). Parameters observed in this study were egg weight loss, air cavity, egg white index, egg yolk index, shell thickness and egg protein quality. The results showed that there was no interaction between the two factors on all research parameters.